Effects of milk bioactive compounds on health - Armand, M.; Flouris, A. D. (Cellular and Molecular Biology, 2013)
Milk provides a rich source of macro- and micro-nutrients, and other more original compounds, the value of which is significant from a nutritional as well as a physiological perspective. Milk proteins have an increased nutritional value that is widely recognised and in many countries dairy products contribute significantly to daily protein intake. The biodefensive properties of mammalian milk proteins as well as the unique biological activities associated with each of them have been widely acknowledged for many years. These aspects are important for the use of milk proteins and milk-protein-derived peptides in dietary and pharmaceutical applications, respectively. Moreover, proteins and peptides influence various health conditions and exert regulatory functions in the human organism. Immunoglobulins are a well-known example of bioactive milk proteins, as they offer an excellent natural defence system to the neonate against bacterial infections. Overall, a large range of bioactivities have been reported for the bioactive compounds contained in milk...